2002
DOI: 10.1073/pnas.072699999
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-amphiphile nanofibers: A versatile scaffold for the preparation of self-assembling materials

Abstract: Twelve derivatives of peptide-amphiphile molecules, designed to self-assemble into nanofibers, are described. The scope of amino acid selection and alkyl tail modification in the peptide-amphiphile molecules are investigated, yielding nanofibers varying in morphology, surface chemistry, and potential bioactivity. The results demonstrate the chemically versatile nature of this supramolecular system and its high potential for manufacturing nanomaterials. In addition, three different modes of self-assembly result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
961
1
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,178 publications
(984 citation statements)
references
References 45 publications
14
961
1
8
Order By: Relevance
“…Photo-crosslinking is suitable for biomedical applications due to the mild and rapid reaction conditions, which can be conducted at Self-assembling PA molecules consist of a hydrophilic peptide segment conjugated to a hydrophobic fatty acid triggering self-assembly of PA molecules into one-dimensional nanostructures in aqueous solution. 52 In addition, it was shown that two oppositely charged PAs carrying different bioactive epitopes can self-assemble into nanofibers at physiological conditions due to electrostatic interactions between ionic amino acids of PAs. 53 Noncovalent forces such as hydrogen bonding, hydrophobic and electrostatic interactions between PAs trigger and stabilize the fiber formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Photo-crosslinking is suitable for biomedical applications due to the mild and rapid reaction conditions, which can be conducted at Self-assembling PA molecules consist of a hydrophilic peptide segment conjugated to a hydrophobic fatty acid triggering self-assembly of PA molecules into one-dimensional nanostructures in aqueous solution. 52 In addition, it was shown that two oppositely charged PAs carrying different bioactive epitopes can self-assemble into nanofibers at physiological conditions due to electrostatic interactions between ionic amino acids of PAs. 53 Noncovalent forces such as hydrogen bonding, hydrophobic and electrostatic interactions between PAs trigger and stabilize the fiber formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A number of molecular designs have been developed for the synthesis of self‐assembling peptide LMWHs with the four main families being amphiphilic peptides, 13, 14, 15 short peptide derivatives, 16, 17, 18, 19, 20 α ‐helix/coil‐coil peptides 21, 22 and β ‐sheet peptides. 4, 23, 24, 25, 26, 27, 28, 29 β ‐sheet peptides are of particular interest as they allow the fabrication of very stable hydrogels with properties that can be tailored through peptide design, media properties and processing.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinspired amphiphilic molecules that exhibit this behavior range from simple di-or tri-peptides6 , 7 to more complex, naturally-occurring peptide motifs such as coiled-coils (i.e., "leucine zipper")8 -10, collagen, elastin-like polypeptides (ELPs) 11 , 12, silk-like polypeptides13 and combinations thereof14, as well as conjugates of peptides with alkyl chains (i.e. peptide amphiphiles) 15 .…”
Section: Introductionmentioning
confidence: 99%